2017
DOI: 10.3168/jds.2016-11526
|View full text |Cite
|
Sign up to set email alerts
|

Machine-learning-based calving prediction from activity, lying, and ruminating behaviors in dairy cattle

Abstract: The objective of this study was to use automated activity, lying, and rumination monitors to characterize prepartum behavior and predict calving in dairy cattle. Data were collected from 20 primiparous and 33 multiparous Holstein dairy cattle from September 2011 to May 2013 at the University of Kentucky Coldstream Dairy. The HR Tag (SCR Engineers Ltd., Netanya, Israel) automatically collected neck activity and rumination data in 2-h increments. The IceQube (IceRobotics Ltd., South Queensferry, United Kingdom) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
144
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(164 citation statements)
references
References 41 publications
(56 reference statements)
15
144
3
2
Order By: Relevance
“…() set the time window as 1 min, and Shen et al. () set the time window as 1 s. Different time windows have also used: 2 hr (Borchers et al., ), 10 s (Martiskainen et al., ), 5 s (Dutta et al., ), and 1–10 min (Diosdado et al., ). When changes in behavior patterns are frequent, the time window should be set for a short range, but it results in a huge data set, making analysis more complicated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…() set the time window as 1 min, and Shen et al. () set the time window as 1 s. Different time windows have also used: 2 hr (Borchers et al., ), 10 s (Martiskainen et al., ), 5 s (Dutta et al., ), and 1–10 min (Diosdado et al., ). When changes in behavior patterns are frequent, the time window should be set for a short range, but it results in a huge data set, making analysis more complicated.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, multiple studies have reported on cow behavior using accelerometers together with machine learning (Borchers et al, 2017;Dutta et al, 2014;Martiskainen et al, 2009). Although there are many methods of machine learning, this study used a simple decision tree.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning approaches recently became the leading technique for object and action recognition in humans (Jain, Tompson, Andriluka, Taylor, & Bregler, 2013;Toshev & Szegedy, 2013). The technique has great potential in animal sciences for studying of different aspects of animal behavior such as movement, food intake, social structure and competition, reproduction behavior, communication and welfare, and nesting using complex datasets (Borchers et al, 2017;Stern, He, & Yang, 2015;Valletta, Torney, Kings, Thornton, & Madden, 2017;Wang, 2019;XU & Cheng, 2017). Automated imaging technologies provide a large number of images that require an efficient strategy of analysis such as machine learning.…”
Section: Discussionmentioning
confidence: 99%
“…As normal daily variation in ruminating time is about 10% (>10% with finely chopped or high-grain diets; Dulphy et al, 1979), the assumption is that large reductions in rumination time by an individual cow on a particular day can be an indication of a change in cow health. For example, rumination time has been shown to be consistently reduced about 8 h before calving and increase about 6 h later, likely a result of limited feed intake (Schirmann et al, 2013;Pahl et al, 2014;Paudyal et al, 2016;Borchers et al, 2017;Kovács et al, 2017). Thus, monitoring rumination time could be useful in predicting time of calving.…”
Section: Detection Of Parturition and Illness In Dairy Cowsmentioning
confidence: 99%